PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KOMPETENSI PROFESIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU DI SMK NEGERI 1 KEDUNGWUNI KABUPATEN PEKALONGAN - Susilo Susilo (JURNAL EDUSCIENCE (JES), 2022)
Abstract This study aims to examine and analyze the role of organizational culture in moderating the effect of professional competence and organizational commitment on teacher performance at SMK Negeri 1 Kedungwuni, Pekalongan Regency. This study with a population of 100 teachers, namely all teachers of SMK Negeri 1 Kedungwuni, Pekalongan districts. The data collection technique used survey methods and the research instrument used a questionnaire with a Likert scale 5. The instrument test was carried out with validity tests through CFA, reliability tests, normality tests, heteroscedasticity tests, and model tests (F test, R-square and sig). Test the hypothesis with quasi-regression analysis, interaction technique by looking at the sig value. The results show that professional competence does not have a positive effect on teacher performance, organizational commitment has a positive effect on teacher performance, organizational culture has a positive effect on teacher performance, organizational culture strengthens professional competence on teacher performance and organizational culture moderates the effect of professional competence has a positive effect on teacher performance in SMK N 1 Kedungwuni, Pekalongan districts, at sig level 0.10, organizational culture strengthens organizational commitment to teacher performance, meaning that organizational culture moderates organizational commitment and has a positive effect on teacher performance at SMK N 1 Kedungwuni, Pekalongan districts.